2009
DOI: 10.1785/0120090038
|View full text |Cite
|
Sign up to set email alerts
|

Fault-Plane Determination of the 18 April 2008 Mount Carmel, Illinois, Earthquake by Detecting and Relocating Aftershocks

Abstract: We developed a sliding-window cross-correlation (SCC) detection technique and applied the technique to continuous waveforms recorded by the Cooperative New Madrid Seismic Network stations following the 18 April 2008 Illinois earthquake. The technique detected more than 120 aftershocks down to M L 1.0 in the 2 week time window following the mainshock, which is three times more than the number of aftershocks reported by the seismic network. Most aftershocks happened within 24 hrs of the mainshock. We then reloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…1 A schematic plot of a typical fault zone, after Chester and Logan (1986) Pinto Mountain faults, Southern California (Fialko et al 2002). In addition, many geophysical methods have been applied in deriving FZ properties such as gravity and electromagnetic surveys, seismic reflection and refraction, travel-time tomography, earthquake location, waveform modeling of FZ-reflected body waves, FZ head waves, and FZ trapped waves (e.g., Mooney and Ginzburg 1986;BenZion and Malin 1991;Ben-Zion et al 1992;Hole et al 2001;Prejean et al 2002;Waldhauser and Ellsworth 2002;Li et al 2002;McGuire and Ben-Zion 2005;Bleibinhaus et al 2007;Li et al 2007;Yang et al 2009;Roland et al 2012). In the following, I briefly review a few seismological and geodetic methods that have been used to derive FZ structure.…”
Section: Fz Properties and Their Effectsmentioning
confidence: 99%
“…1 A schematic plot of a typical fault zone, after Chester and Logan (1986) Pinto Mountain faults, Southern California (Fialko et al 2002). In addition, many geophysical methods have been applied in deriving FZ properties such as gravity and electromagnetic surveys, seismic reflection and refraction, travel-time tomography, earthquake location, waveform modeling of FZ-reflected body waves, FZ head waves, and FZ trapped waves (e.g., Mooney and Ginzburg 1986;BenZion and Malin 1991;Ben-Zion et al 1992;Hole et al 2001;Prejean et al 2002;Waldhauser and Ellsworth 2002;Li et al 2002;McGuire and Ben-Zion 2005;Bleibinhaus et al 2007;Li et al 2007;Yang et al 2009;Roland et al 2012). In the following, I briefly review a few seismological and geodetic methods that have been used to derive FZ structure.…”
Section: Fz Properties and Their Effectsmentioning
confidence: 99%
“…Mori (1996) studied the foreshock (M w 4.3) source processes of the 1992 Joshua Tree Earthquake (M w 6.1) and concluded that a high static stress drop in this foreshock, from a rupture, propagated toward the hypocenter of the main shock. Yang et al (2009) relocated aftershocks and determined the fault plane of the 18 April 2008 Mount Carmel, Illinois earthquake. They concluded that the aftershock distribution was consistent with focal mechanism solutions for the main shock and the four largest aftershocks.…”
Section: Discussionmentioning
confidence: 99%
“…Allmann and Shearer (2007) identified a high-frequency secondary event buried on the rupture plane of the 2004 Parkfield earthquake and concluded that this event was located near the edge of a large asperity. It is recognized that detailed observation and analysis of moderate events should be helpful for understanding the fine structure of source ruptures and the micro-behaviors of earthquake sources physics (Mori 1996;Yang et al 2009). Such analyses can provide significant information relevant to debates on source scaling, stress drop and initial phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMSZ has been a particular focus of attention for seismic studies in the central United States due to the three large M w > 7:0 earthquakes in 1811-1812 (e.g., Nuttli, 1973a;Dunn et al, 2010;Page and Hough, 2014). However, there is evidence of significant potential for large earthquakes outside the NMSZ, such as in the Wabash Valley seismic zone (WVSZ; Nuttli, 1979;Obermeier et al, 1991;Munson et al, 1992;Pavlis et al, 2002;Herrmann et al, 2008;Yang et al, 2009;Hamburger et al, 2011), the region near Marianna, Arkansas, southwest of the NMSZ (Tuttle et al, 2006), the region around the Meers fault, southwestern Oklahoma (e.g., Luza et al, 1987;Kelson and Swan, 1990), and the region northwest of the NMSZ around the Ste. Genevieve fault zone (Heinrich, 1937(Heinrich, , 1949Nuttli, 1973b).…”
Section: Introductionmentioning
confidence: 99%